PENGARUH KUALITAS AUDIT, LIKUIDITAS, PROFITABILITAS, DAN SOLVABILITAS TERHADAP OPINI AUDIT GOING CONCERN PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR INDUSTRI PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA - Mega Arum; Irna Maya Sari (Jurnal Bina Bangsa Ekonomika, 2024)
The purpose of this study is to test whether audit quality, liquidity, profitability and solvency affect the audit opinion of going concern in manufacturing companies in the property and real estate sub-sector listed on the Indonesia Stock Exchange for the period 2018 – 2022. This study uses the purposive sampling method, namely by determining the sample by considering certain criteria. The research sample of 15 companies was taken from the pupulation of manufacturing companies in the industrial and real estate sub-sectors listed on the Indonesia stock exchange for the 2018-2022 period that have met the criteria that have been determined late. The data used is secondary data obtained from the Indonesia Stock Exchange and data analysis using the multicollinearity uni and logistic regression analysis with the SPSS version 25 application. The results of this study are that there is no influence between audit quality, liquidity, profitability and solvency on the audit opinion of going concern in manufacturing companies and property and real estate sub-sectors listed on the Indonesia Stock Exchange for the period 2018 – 2022